How is the Transfer Pricing Concept “Arm’s Length Principle” Applied in Indonesia? - Tambunan, Maria R.U.D. (UI Scholars Hub, 2022)
The research is aimed at analyzing how the arm’s length principle has been applied to transfer pricing cases in Indonesia. The arm’s length principle has become a global formula used by entities to ascertain that the transaction value has been done in an acceptable manner. The arm’s length principle has also become a fundamental basis in Indonesian tax regulations to assess the fairness of price for transactions undertaken by multinational entitles with their affiliation located outside the Indonesia’s jurisdiction. This research used qualitative approach and qualitative research method. The research shows that the manufacturing entities in Indonesia are mostly contract manufacturers which have less risks and non-sophisticated functions. The contribution to global value chain is not substantial. However, the way it has been assessed with regard to its affiliated transaction does not follow its function. The tax authority selected a certain method, transaction net margin method (TNMM) that may be flawed to test the price fairness for such a condition. The test was performed at the level of operating profit of the company without being affected by differences in transactions at the level of operational costs and functions. This behavior could be done differently among individual tax auditors. Therefore, the tax authority may consider institutionalizing a unit to specifically deal with transfer pricing issue.